Hydroxychloroquine affects bone resorption both in vitro and in vivo. Issue 2 (3rd August 2017) - Both, Tim; Zillikens, M. Carola; Schreuders‐Koedam, Marijke; Vis, Marijn; Lam, Wai‐Kwan; Weel, Angelique E. A. M.; van Leeuwen, Johannes P. T. M.; van Hagen, P. Martin; van der Eerden, Bram C. J.; van Daele, Paul L. A.
Abstract : We recently showed that patients with primary Sjögren syndrome (pSS) have significantly higher bone mineral density (BMD) compared to healthy controls. The majority of those patients (69%) was using hydroxychloroquine (HCQ), which may have favorable effects on BMD. The aim of the study was to evaluate whether HCQ modulates osteoclast function. Osteoclasts were cultured from PBMC‐sorted monocytes for 14 days and treated with different HCQ doses (controls 1 and 5 μg/ml). TRAP staining and resorption assays were performed to evaluate osteoclast differentiation and activity, respectively. Staining with an acidification marker (acridine orange) was performed to evaluate intracellular pH at multiple timepoints. Additionally, a fluorescent cholesterol uptake assay was performed to evaluate cholesterol trafficking. Serum bone resorption marker β‐CTx was evaluated in rheumatoid arthritis patients. HCQ inhibits the formation of multinuclear osteoclasts and leads to decreased bone resorption. Continuous HCQ treatment significantly decreases intracellular pH and significantly enhanced cholesterol uptake in mature osteoclasts along with increased expression of the lowdensity lipoprotein receptor. Serum β‐CTx was significantly decreased after 6 months of HCQ treatment. In agreement with our clinical data, we demonstrate that HCQ suppresses bone resorption in vitro and decreases the resorption marker β‐CTx in vivo. We also showed that HCQ decreases the intracellular pH in mature osteoclasts and stimulates cholesterol uptake, suggesting that HCQ induces osteoclastic lysosomal membrane permeabilization (LMP) leading to decreased resorption without changes in apoptosis. We hypothesize that skeletal health of patients with increased risk of osteoporosis and fractures may benefit from HCQ by preventing BMD loss. Abstract : In agreement with our clinical data, we demonstrate that HCQ suppresses bone resorption in vitro and decreases the resorption marker β‐CTx in vivo. We also showed that HCQ decreases the intracellular pH in mature osteoclasts and stimulates cholesterol uptake, suggesting that HCQ induces osteoclastic lysosomal membrane permeabilization (LMP) leading to decreased resorption without changes in apoptosis. We hypothesize that skeletal health of patients with increased risk of osteoporosis and fractures may benefit from HCQ by preventing BMD loss.